Treatment of waste printed circuit board by green solvent using ionic liquid - Zhu, P.; Chen, Y.; Wang, L.Y.; Zhou, M. (Waste management (Elmsford), 2012)
► Recycling waste printed circuit boards (WPCBs) by ionic liquid (IL). ► The epoxy resins of WPCBs are slightly dissolved to produce initial delamination at 240°C. ► The epoxy resins of WPCBs are removed by [EMIM+][BF4-] at 260°C. Recycling of waste printed circuit boards (WPCBs) is an important subject not only for the protection of environment but also for the recovery of valuable materials. A feasibility study was conducted to dissolve bromine epoxy resins of WPCBs using ionic liquid (IL) of 1-ethyl-3-methylimizadolium tetrafluoroborate [EMIM+][BF4-] (nonaqueous green solvent) for recovering copper foils and glass fibers. Experimental results indicated that the initial delamination had seen from the cross-section of the WPCBs by mean of metallographic microscope and digital camera when WPCBs were heated in [EMIM+][BF4-] at 240°C for a duration of 30min. When temperature was increased to 260°C for a duration of 10min, the bromine epoxy resins of WPCBs were throughout dissolved into [EMIM+][BF4-] and the separations of copper foils and glass fibers from WPCBs were completed. This clean and non-polluting technology offers a new way to recycle valuable materials from WPCBs and prevent the environmental pollution of WPCBs effectively.